EDUKASI GIZI PENCEGAHAN STUNTING METODE ANIMASI UNTUK MENINGKATKAN PENGETAHUAN IBU HAMIL TRIMESTER PERTAMA - Siti Nuryawati, Lina; Amalia, Merlly; Antriana, Inna (Jurnal Kesehatan Husada Gemilang, 2025)
Stunting is a growth and development disorder in children caused by chronic nutritional deficiencies and recurrent infections, characterized by a height below normal. The objective of this research is to examine the effect of animation method nutritional education on stunting prevention to improve the knowledge of pregnant women in their first trimester at Sumberjaya Health Center, Majalengka Regency. The study design is a pre-experimental one group pre-test post-test design. The population of this research consists of all pregnant women in their first trimester at Sumberjaya Health Center, Majalengka Regency in 2024, using total sampling technique of 40 participants. The research instrument uses a questionnaire for the pre-test and post-test. Data analysis is performed using the Wilcoxon Test. The univariate results showed that before the counseling was conducted, more than half (57.5%) of first-trimester pregnant women had inadequate knowledge about nutrition to prevent stunting, with an average score of 46.82. After the counseling, more than half (52.0%) had good knowledge with an average score of 70.27. There is an effect of nutrition education on stunting prevention using animation methods on improving the knowledge of first-trimester pregnant women at the Sumberjaya Health Center in Majalengka District (p value = 0.00). It is expected that pregnant women need to have regular check-ups with midwives or doctors, and they should actively seek information from media or health providers to enhance their knowledge in order to prevent stunting in infants and toddlers. Stunting adalah gangguan pertumbuhan dan perkembangan anak akibat kekurangan gizi kronis dan infeksi berulang, ditandai dengan tinggi badan di bawah normal. Tujuan riset ini untuk melihat pengaruh edukasi gizi pencegahan stunting metode animasi untuk meningkatkan pengetahuan ibu hamil trimester pertama di Puskesmas Sumberjaya Kabupaten Majalengka. Desain penelitian pre eksperimen one group pre-test post-test design. Populasi penelitian ini adalah seluruh ibu hamil trimester pertama di Puskesmas Sumberjaya Kabupaten Majalengka Tahun 2024 dengan teknik total sampling sebanyak 40 orang. Instrumen penelitian menggunakan kuisioner untuk pre-test dan post-test. Analisis data dengan Uji Wilcoxon. Hasil univariat menunjukkan sebelum dilakukan penyuluhan lebih dari setengahnya (57.5%) pengetahuan ibu hamil trimester pertama tentang Gizi pencegahan stunting yaitu berpengetahuan kurang dengan rata-rata 46.82, Setelah dilakukan penyuluhan lebih dari setengahnya (52.0%) berpengetahuan baik dengan rata-rata 70,27. Ada pengaruh edukasi gizi pencegahan stunting metode animasi terhadap peningkatan pengetahuan ibu hamil trimester pertama di Puskesmas Sumberjaya Kabupaten Majalengka (p value = 0,00). Diharapkan kepada ibu hamil perlu melakukan pemeriksaan kehamilan secara rutin ke bidan maupun dokter, ibu perlu aktif mencari informasi baik dimedia maupun petugas kesehatan guna menambah pengetahuan, untuk mencegah terjadinya stunting pada bayi balita.